Report on the restoration of wetlands, springs and streams in a mountain landscape - Ivana Bufková (European Journal of Environmental Sciences)
As the ongoing climate change increases water problems, society is starting to understand the importance of re-establishing a functioning water regime in the landscape and restoring wetlands, watercourses and springs. Restoration techniques and methods used in landscapes at low and middle altitudes are relatively well developed. But the same cannot be said for mountainous and hilly areas, which are a challenge hydrologically due to sloping terrain and soil erosion. Restoration technologies in such landscape are still being developed. Upland and hilly areas are, however, an important source of water for lower regions and well-functioning water regime is very important. This also applies to the Šumava region, which is an important spring area, declared as a Protected Area of Natural Water Storage. There have been significant changes in the hydrology in the Šumava Mts. in the past, mainly in drainage. The extent of drainage and its effect on wetlands, springs and watercourses, have been the reason for starting a comprehensive programme of hydrological restoration. The aim of this paper is to show it is possible to restore hydrology in challenging mountain conditions. The micro-catchment approach and water table concept is emphasized. Particular attention is paid to some hidden and still neglected problems, such as drainage of springs and the need for their restoration. This paper summarizes the results and experiences gained during 25 years of restoration (1999–2024). During that time, a total of 296 km of drainage channels were blocked in the Šumava region, 36 km of small mountain streams and 28 spring areas were restored. The total area of hydrological restoration is 2718 ha. The cross-border LIFE for MIRES project (2018–2024), currently in its final year, played an important role in this achievement.